2017
DOI: 10.1007/s00204-017-1950-9
|View full text |Cite
|
Sign up to set email alerts
|

The highly bioactive molecule and signal substance 6-formylindolo[3,2-b]carbazole (FICZ) plays bi-functional roles in cell growth and apoptosis in vitro

Abstract: The maintenance of cellular homeostasis is a complex process that is governed by the receipt of prototypical growth and death signals. The endogenous functions of aryl hydrocarbon receptor (AHR) in cellular homeostasis are not well understood. We aimed to establish whether the disturbance of endogenously activated AHR can influence cell growth, and if so, what mechanism(s) are involved. Cell growth was measured in mouse hepatoma Hepa-1 wild-type and cytochrome P4501A1 (CYP1A1)-deficient c37 cells. In other set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…In this study, we have found that up‐regulation of CYP1A1 required relatively reducing conditions as shown by measurement of cellular GSH/GSSG ratio and redox state which was in correlation with CYP1A1 transcription and enzyme activities in vivo and in vitro. Down‐regulation of CYP1A1 by oxidants has been reported earlier in several studies . We and the other researchers have shown that CYP1A1 can be down‐regulated under oxidative stress conditions .…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we have found that up‐regulation of CYP1A1 required relatively reducing conditions as shown by measurement of cellular GSH/GSSG ratio and redox state which was in correlation with CYP1A1 transcription and enzyme activities in vivo and in vitro. Down‐regulation of CYP1A1 by oxidants has been reported earlier in several studies . We and the other researchers have shown that CYP1A1 can be down‐regulated under oxidative stress conditions .…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, mulberry extracts were found to impair the skin damage induced by B[a]P through the inhibition of the AhR signaling (Woo, Lee, Park, & Jung, 2017). As a compound, FICZ plays a bifunctional role in cell growth and apoptosis, which depends heavily on its concentration and cell type (Mohammadi‐Bardbori et al, 2017). A high concentration of FICZ (such as 1 µM) can induce sustained CYP1A1 activity and trigger a cascade of cellular events.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the discovery of the endogenous AhR ligand and FICZ treatment led to the overexpression of miR‐206, miR‐133a, and miR‐27b in an AhR‐dependent manner is new in this study (Figure ). In our previous study, we showed that by increasing the levels of the endogenous ligand FICZ, CYP1A1 inhibitors change cell growth kinetics and trigger apoptosis through a mitochondrial‐dependent pathway . miR‐27b‐3p interacts with the 3′‐untranslated region of cytochrome P450 1B1 (CYP1B1) and the product of this enzyme is assumed to be involved in the metabolic activation of procarcinogens .…”
Section: Discussionmentioning
confidence: 99%
“…FICZ has been shown to play an important role in several physiological pathways, such as the modulation of the immune system, regulation of circadian rhythms, and skin homeostasis . In addition, FICZ in a regulatory feedback mechanism, which can be efficiently metabolized by the cytochrome P450 family 1 enzymes, especially CYP1A1, CYP1A2, and CYP1B1 . Some of the most important enzymes under the regulatory control of AhR are CYP1A1 and CYP1B1, which catalyze the metabolic activation of 17β‐estradiol (E2) at the C‐2 and C‐4 positions, respectively .…”
Section: Introductionmentioning
confidence: 99%